Risk Factors for Febrile Seizures in Children Aged 6 – 59 Months in Surabaya, East Java - Febrianto Adi Husodo; Sitti Radhiah; Pramita Anindya Nugraheni (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Febrile seizures are common in children under 5 years of age. Parents are concerned when their children have seizures; therefore, it is necessary to provide promotive and preventive education regarding the risk factors for febrile seizures so that parents are more prepared. This study aimed to explore the risk factors for febrile seizures in children.Methods: This case-control study was conducted on 170 children. Sampling was carried out by purposive sampling on inpatients and/or outpatients at the Pediatric Department Dr. Ramelan Naval Hospital Surabaya during May 2019-July 2020. Secondary data for children with fever were retrieved from medical records, with seizures (n85) and without seizures (n85) as a control group. Furthermore, data on temperature, age, birth weight, and history of asphyxia were analyzed and compared, using the chi-square test or Fisher’s exact test.Results: There was a significant difference between the case and control groups regarding the history of asphyxia and the occurrence of febrile seizures (p=0.002; OR=26.39; and 95% CI 1.52-455.62). There was no significant difference between the risk factors for high temperature (p=0.12), age (p=0.52), or birth weight (p=0.37) with the occurrence of febrile seizures.Conclusions: A history of asphyxia in children under five years is a risk factor for febrile seizures. Appropriate education from health professionals can help parents improve their knowledge, attitudes, and practices in dealing with febrile seizures and their risk factors.